2014
DOI: 10.1002/jmv.24045
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and occult hepatitis B virus infection in young adults in Banjarmasin, Indonesia

Abstract: Hepatitis B virus (HBV) infection remains a public health problem in Indonesia. There has been limited data regarding HBV infection in young adult population. This study aimed to evaluate the seroepidemiology of HBV infection and characterize occult HBV variants in healthy young adults in Banjarmasin, Indonesia, who were born before the implementation of the universal infant hepatitis B vaccination. Serum samples of 195 healthy young adults were tested for HBsAg, anti-HBc, and anti-HBs. The prevalence of HBsAg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 57 publications
5
16
0
Order By: Relevance
“…The adjusted seroprevalence of HBsAg in South Korea in 2009 was 4%, which was in agreement with the current study (15). The prevalence of HBsAg in young adults in Banjarmasin, Indonesia was 4.6% (28). Recently a report indicated that a low dose of RPB5-mediating protein (RMP) could inhibit HBV transcription and replication (29).…”
Section: Discussionsupporting
confidence: 89%
“…The adjusted seroprevalence of HBsAg in South Korea in 2009 was 4%, which was in agreement with the current study (15). The prevalence of HBsAg in young adults in Banjarmasin, Indonesia was 4.6% (28). Recently a report indicated that a low dose of RPB5-mediating protein (RMP) could inhibit HBV transcription and replication (29).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, HBsAg positivity was higher among older people (12). Additionally, the prevalence of HBsAg in young adults in Banjarmasin, Indonesia, was 4.6% (13). Furthermore, a comprehensive study in Singapore showed that the prevalence of HBsAg seropositivity was 3.6% in 2010 (14).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the Y100C mutation was also detected in HBsAg-positive patients analyzed here and elsewhere [Santos et al, 2004]. As previously reported, the T131N mutation has been associated with failure to detect HBsAg by immunoassays and immune escape to HBV vaccine/ immunoglobulin [Svicher et al, 2011;Darmawan et al, 2015]. The patient V-68 showed, in addition to Y100C and T131N, the D144A substitution, which has also been associated with vaccine escape or immunoglobulin therapy failure, diagnostic problems, and OBI [Huang et al, 2012;Ma and Wang, 2012].…”
Section: Discussionsupporting
confidence: 78%